The Effect of Language Games Toward Mastery Students Vocabulary at Seventh Grade of SMP Islam Al-Ikhlas - Ni’maturrohmah Ni’maturrohmah; Syaeful Millah (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2022)
The main objective of the study was to determine whether playing Taboo games could affect students' language retention or not. This study focused on 40 students in grade VII at SMP Islam Al-Ikhlas Bekasi during the academic year 2021–2022. In this study, every student was chosen as a sample (class VII-3 and VII-4). With the design of the class control and class experimental, the methodology utilized in this work is quantitative. Using SPSS statistic 26, a statistical analysis of the pre-test and post-test data was conducted. According to the study's findings, the pre-test mean score for the students was 65.40, while the post-test mean score was 86.55. The t-test of students’ achievement in experimental and control group in posttest was smaller than sig. (2-tailed) is 0,000 < 0,05. It means that Taboo games has significant effect on student’s vocabulary students at SMP Islam A-Ikhlas Bekasi.